An Inexpensive 6D Motion Tracking System for Posturography - Figtree, William V. C.; Migliaccio, Americo A. (Frontiers in Neurology, 2018)
Computerised posturography is most often performed with a force plate measuring centre-of-pressure (COP). COP is related to postural control actions but does not monitor the outcome of those actions, i.e., centre-of-mass (COM) stability. For a more complete analysis of postural control COM should also be measured; however, existing motion tracking technology is prohibitively expensive and overcomplicated for routine use. The objective of this work was to create and validate an inexpensive and convenient stereo vision system which measured a trunk-fixed target’s 3D position and orientation relating to COM. The stereo vision system would be complementary to typical force plate methods providing precise 6D position measurements under laboratory conditions. The developed system’s measurement accuracy was worst in the inferior-superior axis (depth) and pitch coordinates with accuracy measures 1.1 mm and 0.8° respectively. The system’s precision was worst in the depth and roll coordinates with values 0.1 mm and 0.15° respectively. Computer modelling successfully predicted this precision with 11.3% mean error. Correlation between in vivo target position and COP was above 0.73 with COP generally demonstrating larger excursions oscillating around target position. Power spectral analysis of target position revealed 99% of the signal was bound below 1.1 Hz matching expectations for COM. The new complementary measurement method enables identification of postural control strategies and as a result more complete analysis. Stereo vision is a useful complement to typical force plate equipment. The system presented here is inexpensive and convenient demonstrating potential for routine use in clinic and research. In order to use this system in clinic, future work is required in interpretation of this system’s data and normal reference values must be established across gender and age in a healthy population followed by values from patients with different pathologies.